2011
DOI: 10.3732/ajb.1000407
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of 21 EST‐derived microsatellite markers in Vicia faba (fava bean)

Abstract: These markers will be useful to study genetic diversity, genetic mapping, and molecular breeding in fava bean.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 9 publications
3
24
0
Order By: Relevance
“…Ovesna et al [25] also reported that high number of allele was in accordance with high gene diversity in the study aiming to identify of Czech garlic varieties using 14 SSR markers. The number of allele and gene diversity in the present study coincided with Ma et al [26], who found the former between 2 and 9, and the latter between 0.0476 and 0.8304 in the study employing 32 accessions of V. faba and 21 microsatellite markers. Moreover, Gong et al [27] stated the number of allele varying from 1 to 3, and expected heterozygosity from 0 to 0.64 in the study Figure 1.…”
Section: Resultssupporting
confidence: 74%
“…Ovesna et al [25] also reported that high number of allele was in accordance with high gene diversity in the study aiming to identify of Czech garlic varieties using 14 SSR markers. The number of allele and gene diversity in the present study coincided with Ma et al [26], who found the former between 2 and 9, and the latter between 0.0476 and 0.8304 in the study employing 32 accessions of V. faba and 21 microsatellite markers. Moreover, Gong et al [27] stated the number of allele varying from 1 to 3, and expected heterozygosity from 0 to 0.64 in the study Figure 1.…”
Section: Resultssupporting
confidence: 74%
“…Moreover, our data revealed that the number of alleles detectable in Tunisian faba bean populations is comparable with the number of alleles detected in traditional Korea population (Suresh et al 2013). On the other hand, the mean number of alleles was high (6.62) compared with the mean number of alleles per locus for China and some Europen (2.76) faba bean genotypes (Ma et al 2011). These data suggested that Tunisian faba bean populations are polymorphic, providing a large number of alleles within populations.…”
Section: Discussionmentioning
confidence: 75%
“…Eight simple sequence repeat (SSR) primer pairs were used for molecular analyses. Six primer pairs were obtained from Ma et al (2011): SSR3, SSR4, SSR5, SSR6, SSR7 and SSR8, and two primer pairs were obtained from Gong et al (2010): SSR1 and SSR2. The PCR reactions were carried out in a volume of 25 ll containing 50 ng genomic DNA, 0.3 lM forward and reverse primers, 2 mM MgCl 2 , 0.3 mM dNTPs, 1U Taq DNA polymerase (Thermo Fisher Scientific, Germany), in 1xPCR buffer (10 mM Tris-HCl, pH 8.3 and 50 mM KCl).…”
Section: Molecular Analysismentioning
confidence: 99%
“…Among them, 128 SSR markers were referred to in Ma et al [25], 236 SSR markers were selected from a linkage map developed by El-Rodeny et al [26], and the remaining SSR markers (unpublished data) were kindly provided by the Institute of Crop Science, Chinese Academy of Agricultural Sciences (ICP, CAAS). The ISSR markers used in this study were according to Zietkiewicz et al [27].…”
Section: Marker Analysismentioning
confidence: 99%
“…The SSR markers were firstly randomly selected from each linkage group (LG) according to Ma et al [25] and El-Rodeny et al [26]. Also subsequently, unpublished SSR markers (including EST sequences) were kindly provided by the Institute of Crop Science, Chinese Academy of Agricultural Sciences (ICP, CAAS).…”
Section: Ssr and Issr Markersmentioning
confidence: 99%